Pembangunan dan Edukasi Greenhouse Hidroponik sebagai Upaya Peningkatan Ketahanan Pangan Lokal di Desa Nanggerang Kecamatan Tajur Halang Bogor - Nur Azhima; Siti Aminah; Siti Lutfi Latifah; Tri Isniarti Putri; Siti Salma As Shiddiqah; Tubagus Zeid Fathurroji; Fadhilaturrohmadhoni Jidan; Fathia Asheila Salma; Aditiya Darmadi. (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Community Service Program (KKN) is one form of student service to the community through practical activities focused on empowerment. One of the reasons for constructing a hydroponic greenhouse in Nanggerang Village is the scarcity of household land and the low utilization of modern agricultural technology. In addition to the greenhouse construction, the KKN Group 15 (Narasaka) team provided simple training on plant cultivation using a basic hydroponic system with recycled plastic bottles to reduce plastic waste. This program aims to offer an efficient, environmentally friendly alternative for farming, as well as enhance the community's knowledge and skills in sustainable agriculture. In this community service activity, the methods used were problem observation, preparation of tools and materials, verbal socialization, and construction. With this program, it is hoped that the community of Nanggerang Village will gain knowledge about hydroponic systems and be able to apply simple hydroponic cultivation at their respective homes, even with limited land. The conclusion from the construction and education efforts is that the limited land available in the community of Nanggerang Village and other areas in Indonesia can be utilized through smart farming methods such as productive and economically valuable hydroponics.